Avaliação da espermatogênese, níveis plasmáticos de esteroides sexuais e expressão de HSP70, PCNA e caspase-3 em Prochilodus argenteus: um estudo comparativo em dois pontos do rio São Francisco, a jusante da barragem de Três Marias - Fabricio Flavio Theophilo Domingos (2012)
The testicular development and maturation of fish are regulated by sex hormones that influence the processes of proliferation and cell death of germ and somatic cells. The stress caused by changes in environmental conditions induces the expression of heat shock proteins (HSPs) which have a key role in testis homeostasis. The objective of this work was to evaluate the testicular maturation, spermatogenesis, plasma levels of sex steroids as well as the expression of HSP70, cell proliferation (PCNA) and apoptosis (TUNEL and caspase-3) in testis of the curimatã-pacu Prochilodus argenteus. Thus, the study was performed in three steps. Initially we evaluated spermatogenesis and sex steroid levels in the curimatã-pacu collected at two sites in the São Francisco River, downstream from the Três Marias dam. During the reproductive period, the volumetric proportion and number of spermatogonia cysts were significantly higher in fish from site 1, immediately downstream from the dam, where cell proliferation and apoptosis were higher during spermatogonial phase. In fish from site 2, the morphometric parameters as well as the PCNA and TUNEL reactions were higher in spermatocytes cysts. These results associated with the seasonal changes of the testicular activity, levels of testosterone, 17 -estradiol, 17-hydroxyprogesterone and gonadosomatic index indicated that spermatogenesis of P. argenteus is more active in fish captured in site 2, after the confluence with the Abaeté River. In the second step, we studied the expression of HSP70, PCNA and caspase-3 during the reproductive cycle of P. argenteus captured after the confluence with Abaeté River, where environmental conditions are favorable for the reproduction of the species. The levels of HSP70 increased significantly in testis from June to December (resting to testicular maturation) decreasing in March (testicular regression). The labelling of PCNA followed the seasonal variations of the testicular activity, being predominant in type A spermatogonia in June and in type B spermatogonia in June, September and March, while primary spermatocytes were particularly marked in December. The TUNEL-positive reaction was detected in the nucleus of germ cells at all stages of development, except in spermatozoa. Enzymatic activity of caspase-3 decreased from June to December, increasing in March. These results suggest that HSP70 may protect the germ cells from caspase-3-dependent apoptosis during testicular. In the third step, we studied the levels of HSP70 and caspase-3 as a biomarker of environmental impact using testis and liver of P. argenteus. The levels of HSP70 and caspase-3 in testis and liver were significantly higher in fish collected at site1 during the rainy season compared to the dry season. Thus, our results demonstrate that morphometric analysis, levels of sex steroids and protein levels of HSP70, PCNA and caspase-3 can provide useful tools for the assessment of spermatogenesis in fish populations in natural environments.